Reading research and the promotion of reading outside the school: A comprehensive review of empirical research - Van Daal, Victor H.P.; Miglis Sandvik, Jenny (International Journal about Parents in Education, 2023)
A basic skill like reading is usually acquired in lower primary education. However, reading can and should also be promoted outside the school in order to provide the best learning opportunities for every student. In this review, it is first looked at what reading is. Then it is discussed where the large individual differences in reading skill come from. Finally, the reading research upon which initiatives for promoting reading outside the school are based and recommendations as to what to do for different age levels are presented.